Prevalence of gingival overgrowth induced by antihypertensive drugs: A hospital-based study - Saumiya Gopal; Rosamma Joseph; Vediyera Chandroth Santhosh; Vadakkedath Venugopal Harish Kumar; Shiny Joseph; Abhijeet Rajendra Shete (Journal of Indian Society of Periodontology, 2015)
Background: Gingival overgrowth (GO) is a known side-effect of calcium channel blockers. Although there have been several case reports, few studies have examined the prevalence of nifedipine, diltiazem, and amlodipine. This study was conducted to determine the prevalence and risk factors for GO in patients treated with calcium channel blockers. Materials and Methods: A cross-sectional study was conducted in out patient Department of Medicine, Government Medical College, Calicut. 133 patients taking antihypertensives were examined for the presence of GO using two different indices: Vertical GO in 6 points around each tooth and horizontal Miranda-Brunet index in the interdental area. Gingival index (GI), plaque index, and probing depth were also evaluated. Results: The frequency of GO was significantly higher in nifedipine-treated cases than other drug groups. Frequency of GO was 75% for nifedipine, 31.4% for amlodipine and 25% for amlodipine + metoprolol. Higher gingival, plaque and calculus were observed in patients taking calcium channel blockers. Among the possible risk factors, only the GI showed a significant correlation with GO. Conclusions: Patients taking antihypertensives had poor oral hygiene. Patients taking nifedipine showed a higher frequency of GO. Gingival inflammation acts as a predisposing factor.